Առաքելական Սուրբ Եկեղեցին եւ հայ հոգեւորականութիւնը Ալեքսանդր Շիրվանզադէի նամակներում - Պետրոսեան, Յասմիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается отношение и восприятие Армянской Апостоль- ской Церкви и её духовенства в личной переписке (публикуемой впервые) известного армянского писателя и мыслителя Александра Ширванзаде. Анализируются как частные письма, наполненные эмоциональными суждениями и личными впечатлениями о таких церковных деятелях, как епископы Магакия Орманян и Гарегин Срвандзтян, так и официальные обращения к иерархам Церкви — католикосам Мкртичу Хримяну и Маттеосу Измирлянцу. The article explores the attitude toward and perception of the Armenian Apostolic Church and its clergy in the private correspondence (published here for the first time) of the renowned Armenian writer and intellectual Alexander Shirvanzade. It analyzes both personal letters, filled with emotional judgments and personal impressions of such ecclesiastical figures as Bishops Maghakia Ormanian and Garegin Srvandztyan, as well as official appeals addressed to church hierarchs — Catholicoi Mkrtich Khrimian and Matteos Izmirlian.
Keywords: Հաղորդումներ; Բանասիրութիւն